Fine-needle aspiration cytology as a diagnostic modality for cysticercosis: A clinicocytological study of 137 cases - Pooja Kala; Pratima Khare (Journal of Cytology, 2014)
Background: Cysticercosis, a parasitic tissue infection caused by the larva of Taenia solium, is quite a common disease in our part of the world, but its incidence is often underestimated. Fine-needle aspiration cytology (FNAC) plays an important role in early detection of this disease, especially when the lesion is located in anatomically approachable superficial locations. Aims: The aim was to study role of FNAC in the diagnosis of cysticercosis. Materials and Methods: In this retrospective study, the data of 137 patients with palpable nodules, who were diagnosed as having or suspicious of cysticercosis on FNAC, were retrieved and analyzed. Results: In 129 (94.2%) cases, a definitive diagnosis of cysticercosis was obtained in the form of parts of parasite tegument, hooklets, parenchymatous portion and calcareous corpuscles. In the background, giant cells, mixed inflammatory cells, and epithelioid cells were present. In remaining 8 (5.8%) cases, larval fragments could not be identified on the aspirates, and the diagnosis of parasitic inflammation was suggested on the basis of other cytological findings such as clear fluid aspirate, presence of eosinophils, histiocytes, foreign body giant cells, a typical granular dirty background, etc. Follow-up biopsy in these 8 cases confirmed the diagnosis of cysticercosis in 7 (87.5%) while in 1 (12.5%) case, histopathology was suggestive of parasitic cyst. Conclusion: Fine-needle aspiration cytology in cysticercosis is a low-cost outpatient procedure. The cytological diagnosis is quite straightforward in cases where the actual parasite structures are identified in the smears. In other cases, a cytological diagnosis of suspicious of cysticercosis can be given if the cytological findings suggest the same.